Thermodynamic and Structural Analysis of DNA Damage Architectures Related to Replication. (28th April 2013) - Amato, Nicholas J.; Mwai, Christopher N.; Mueser, Timothy C.; Bryant-Friedrich, Amanda C.
Abstract : Damaged DNA, generated by the abstraction of one of five hydrogen atoms from the 2′-deoxyribose ring of the nucleic acid, can contain a variety of lesions, some of which compromise physiological processes. Recently, DNA damage, resulting from the formation of a C3′-thymidinyl radical in DNA oligomers, was found to be dependent on nucleic acid structure. Architectures relevant to DNA replication were observed to generate larger amounts of strand-break and 1-(2′-deoxy- β -D- threo -pentofuranosyl)thymidine formation than that observed for duplex DNA. To understand how this damage can affect the integrity of DNA, the impact of C3′-thymidinyl radical derived lesions on DNA stability and structure was characterized using biophysical methods. DNA architectures evaluated include duplex DNA (dsDNA), single 3′ or 5′-overhangs (OvHgs), and forks. Thermal melting analysis and differential scanning calorimetry measurements indicate that an individual 3′-OvHg is more destabilizing than a 5′-OvHg. The presence of a terminal 3′ or 5′ phosphate decreases theΔ G 25 to the same extent, while the effect of the phosphate at the ss-dsDNA junction of OvHgs is dependent on sequence. Additionally, the effect of 1-(2′-deoxy- β -D- threo -pentofuranosyl)thymidine is found to depend on DNA architecture and proximity to the 3′ end of the damaged strand.